Menelisik Minat UMKM Menerapkan Pembukuan Menggunakan Theory Of Planned Behavior - Ming Chen; Andrew Gunawan; Heriyanto (Owner : Riset dan Jurnal Akuntansi, 2023)
This research was conducted to explore the root of the problem that causes micro-entrepreneurs to want or not to carry out bookkeeping. Bookkeeping itself is the foundation of an effort to record income and expenses in a period. Bookkeeping is the basic foundation for providing accounting information to micro and small scale businesses, especially for decision making, so it is interesting to study. This research will be conducted on micro-enterprises in the city of Palembang, bearing in mind that there are still many micro-enterprises that have not kept bookkeeping. The sample selection technique in this study used a purposive sampling method. This study uses SPSS 23. The results in this study are that behavior has no effect on interest, subjective norms and behavioral control have a positive effect on the interest of MSME actors in the city of Palembang.